A simple hybrid redundancy strategy accompanied by simplified swarm optimization for the reliability–redundancy allocation problem. Issue 3 (4th March 2022) - Hsieh, Tsung-Jung
Abstract : In this study, a new strategic model called Markov-based cold standby combined with components mixing (RRAP-CM-MCCS), is proposed to improve system reliability. The optimization method used here is simplified swarm optimization (SSO), in which SSO adopts a multi-role resource sharing strategy to provide the diverse system components required by RRAP-CM-MCCS. The diversity here lies in providing every component in a subsystem with its own failure rate as a decision variable in addition to determining the corresponding reliability of each component. Consequently, compared to the state-of-the-art results in the literature, not only can the system reliability be improved, but the combination of multiple configurations also enables relevant required resources to be saved.